Are prehospital treatment or conveyance decisions affected by an ambulance crew's ability to access a patient's health information?. Issue 1 (December 2015) - Zorab, Ollie; Robinson, Maria; Endacott, Ruth
Abstract Background A shift from a predominantly emergency service, towards one where a wide range of conditions are managed and treated on scene presents numerous challenges for ambulance services and clinicians. The effective management of a broad range of patients and conditions in the ambulance setting will have an impact on other parts of the health service including emergency departments and primary care. Methods A two part online survey was distributed to operational staff working for a regional UK ambulance service. Clinicians were asked to report their experiences of accessing patient information and making decisions about patient management based on four hypothetical patient scenarios. Results A survey of clinical staff (n = 302) revealed that (i) the vast majority experienced difficulties in accessing patients' health information, (ii) this was particularly true in the out of hours period and (iii) They felt that better access would likely lead to more appropriate selection of care pathways. Conclusions Decisions regarding the most appropriate care for patients presenting to the ambulance service are best informed by access to accurate and complete health information and records. An understanding of patients' pre-existing medical conditions, recent treatments and health information is needed for the selection of the most appropriate care; this information is often difficult to obtain in the ambulance service setting.